Peak car and increasing rebound: A closer look at car travel trends in Great Britain. (June 2017) - Stapleton, Lee; Sorrell, Steve; Schwanen, Tim
Highlights: We find that income, fuel costs and urbanisation are the main drivers of car travel trends in GB. Urbanisation may be a proxy for several factors contributing to changes in car use. We estimate the direct rebound effect for car travel in Great Britain to be around 26% We estimate that the direct rebound effect has increased over time. Abstract: This paper uses econometric analysis of aggregate time-series data to explore how different factors have influenced the demand for car travel in Great Britain since 1970 and how the rebound effect has changed over that time. Our results suggest that changes in income, the fuel cost of driving and the level of urbanisation largely explain travel trends over this period – with recent reductions in car travel (peak car) being driven by a combination of the rising fuel cost of driving, increased urbanisation and the economic difficulties created by the 2008 financial crisis. We find some evidence that the proportion of licensed drivers has influenced aggregate travel trends, but no evidence that growing income inequality and the diffusion of ICT technology have played a role. Our results also suggest that the rebound effect from improved fuel efficiency has averaged 26% over this period and that the magnitude of this effect has increased over time. However, methodological and data limitations constrain the level of confidence that we can have in these results.